2013
DOI: 10.4081/jlimnol.2013.e41
|View full text |Cite
|
Sign up to set email alerts
|

Aphanizomenon gracile increases in width in the presence of Daphnia. A defence mechanism against grazing?

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Thus, a long-term absence of grazers may remove the selection against mutation leading to increase the variability in filament thickness and abnormalities in cyanobacterial cultures. This view may be supported by previous studies of Cerbin et al, 2013, in which the thickness of the same strain of A. gracile increased after a 12-day exposure to daphnids and infochemicals of these animals.…”
Section: Discussionsupporting
confidence: 72%
“…Thus, a long-term absence of grazers may remove the selection against mutation leading to increase the variability in filament thickness and abnormalities in cyanobacterial cultures. This view may be supported by previous studies of Cerbin et al, 2013, in which the thickness of the same strain of A. gracile increased after a 12-day exposure to daphnids and infochemicals of these animals.…”
Section: Discussionsupporting
confidence: 72%
“…in Daphnia's guts, while wider filaments became stuck and crowded closely together in the mouth. Moreover, Cerbin et al (2013) observed a widening of A. gracile's filaments in the presence of Daphnia, which was interpreted as a defence mechanism against grazing. These results suggest that filament width can shape the interactions between Daphnia and filamentous cyanobacteria.…”
Section: Introductionmentioning
confidence: 89%
“…In addition, it would be also worth studying how the present model could fit into the survival of filamentous MC-producing cyanobacteria e.g., Planktothrix agardhii, which are not known to form colonies. However, under some stress stimuli, P. agardhii can increase in width, which might be involved in an adaptive defense mechanism [107].…”
Section: Future Research Prospectsmentioning
confidence: 99%